2003
DOI: 10.1590/s0036-36342003001000006
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Mexican women: a public health problem

Abstract: Objective. The purpose of this study is to quantify the prevalence and distribution of anemia among women of childbearing age (12 to 49 years) participating in the 1999 National Nutrition Survey (NNS-1999). Material and Methods. The survey had a probabilistic design and was representative at the national level, of urban and rural areas and four regions: North, South, Center, and Mexico City. Hemoglobin concentration was determined in capillary blood samples using a portable photometer (HemoCue), in 17 194 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 20 publications
2
28
0
6
Order By: Relevance
“…An analysis carried out with indigenous women from Suruí (from the Indigenous Location Sete de Setembro, located between the States of Rondônia and Mato Grosso) corroborates this study, since the levels of hemoglobin presented linear reduction with the reduced socioeconomic status, thus increasing the prevalence of anemia in this group 8 . Shamah-Levy et al 29 also found significance in the variable socioeconomic condition after the multivariate adjustment with anemia in Mexican women.…”
Section: Discussionmentioning
confidence: 89%
“…An analysis carried out with indigenous women from Suruí (from the Indigenous Location Sete de Setembro, located between the States of Rondônia and Mato Grosso) corroborates this study, since the levels of hemoglobin presented linear reduction with the reduced socioeconomic status, thus increasing the prevalence of anemia in this group 8 . Shamah-Levy et al 29 also found significance in the variable socioeconomic condition after the multivariate adjustment with anemia in Mexican women.…”
Section: Discussionmentioning
confidence: 89%
“…Shamah-Levy et al 32 , estudando 17.194 mulheres mexicanas, encontraram que no conjunto de variáveis significativamente associadas à anemia (área geográfica, idade, paridade, escolaridade, estrato socioeconômico, etnia), apenas a região geográfica (urbana/rural), paridade e condição socioeconô-mica foram mantidas no modelo final.…”
Section: Resultsunclassified
“…En nuestro estudio, la diferencia porcentual de las prevalencias urbanas y rurales es de más de ocho puntos, no obstante, en otros contextos, como el de México, esta no presenta diferencias en sus proporciones según áreas de residencia, por lo que sería interesante, estudiar esta característica, y comparar resultados con Perú (19) . En contraste con nuestros hallazgos, un estudio en Haití reportó que la mayor parte de la población de mujeres anémicas en edad gestacional vivía en áreas urbanas, respondiendo a diferentes factores que en las comunidades rurales (quintil de ingresos y empleo), viéndose asociados en cambio, con el nivel educativo y sobrepeso (20) .…”
Section: Discussionunclassified